Effectiveness of Response Inhibition Training and Its Long-Term Effects in Healthy Adults: A Systematic Review and Meta-Analysis - Li, Wanyue; Shang, Yaru; Zhuang, Weisheng; Mai, Wangxiang; Cheng, Wenwen; Chen, Zhuoming (Frontiers in Neuroscience, 2022)
Abstract Objective: This study aims to evaluate the effectiveness and long-term effects of response inhibition training as a therapeutic approach in healthy adults. Methods: The PubMed, Embase, Web of Science, China National Knowledge Infrastructure (CNKI), Wanfang, and China Science and Technology Journal Database (VIP) were searched for studies. Data on the improvement of Cognitive function and its long-term effect were extracted by two authors independently. The pooled data were meta-analyzed using a random-effects model, and the quality of each eligible study was assessed by The Cochrane Collaboration’s tool. Results: 9 articles were included. 1 of the articles included 2 trials, so 10 eligible trials(response inhibition training group vs control group) were identified. A total of 490 patients were included. Response inhibition training has beneficial effects on improving cognitive function in healthy adults compared to control treatment(SMD, -0.93; 95% CI, -1.56 to -0.30; Z=2.88, P=0.004), the subgroup analysis results showed that either GNG training alone(SMD, -2.27; 95% CI, -3.33 to -1.21; Z=4.18, P<0.0001) or the combination of both SST and GNG significantly improved cognitive function in healthy adults(SMD, -0.94; 95% CI, -1.33 to -0.56; Z=4.80, P<0.0001), whereas SST training alone did not have such an effect(SMD, -0.15; 95% CI, -0.76 to 0.47; Z=0.47, P=0.64). But its long-term effects are not significant (SMD, -0.29; 95% CI, -0.68 to 0.10; Z=1.45, P=0.15). The subgroup analysis results showed that neither GNG training alone(SMD, -0.25; 95%CI, -0.75 to 0.24; Z=0.99, P=0.32) nor SST training alone(SMD, 0.03; 95% CI, -0.42 to 0.48; Z=0.14, P=0.89) could improve the cognitive function of healthy adults in the long term. In contrast, the combination of both training(SMD, -0.95; 95% CI, -1.46 to -0.45; Z=3.68, P=0.0002) can have long-term effects on the improvement of cognitive function in healthy adults. Conclusions: The findings of our study indicate that response inhibition training can improve the cognitive function of healthy adults and that more RCTs need to be conducted to validate their usefulness in clinical cases.